Penggunaan Media Gambar Untuk Meningkatkan Kemampuan Bercerita Terhadap Mata Pelajaran Bahasa Indonesia Kelas III SD Plus Babussalam - Ani Sri Mulyani; Hani, Umi; Muhammad Jamil Arifillah; Masripah, Imas (Prodi PGMI STAI Sabili Bandung, 2022)
This study aims to explain the use of media images in teaching Indonesian storytelling for class III elementary school students and improve students' storytelling skills. In this study, the theory of Djunaidi & Fauzan (2012) was used. This study uses a qualitative method that is descriptive, this research will explain the facts and characteristics factually and carefully which will later be drawn conclusions. Participants in this study consisted of 25 students and 1 teacher. In this study, data were collected by observation, tests and interviews. The results of the study showed that learning using picture media was proven to be able to improve students' storytelling abilities in class III Indonesian language learning at SD Plus Babussalam. The increase in students' storytelling ability can be seen from the observation results which increased several points and the test results which experienced an increase. Apart from observations and tests, the results of the interviews also show that the use of media images can attract students' attention so that the ability to tell stories also increases.